2022
DOI: 10.48550/arxiv.2201.07293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape of heavy baryons from the perspective of the chiral quark-soliton model

Maxim V. Polyakov,
Michal Praszalowicz

Abstract: We employ the Chiral Quark-Soliton Model and the heavy quark symmetry to describe spectra of charm and beauty baryons. Heavy baryons can be classified according to the SU(3) representations of the light sector. We argue that recently discovered Ξ b states can be interpreted as negative parity excited anti-triplets or sextets, and the Σ b states as negative parity sextets. Consequences of such assignments for the decay patterns are discussed and also predictions of masses of the yet unmeasured sextet members ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Theoretical studies based on the chiral quark-soliton model can be found in Refs. [358,359,360,361], and these results possibly support the Ω c (3050) and Ω c (3119) as exotic heavy pentaquark baryons. See Refs.…”
Section: 23mentioning
confidence: 63%
“…Theoretical studies based on the chiral quark-soliton model can be found in Refs. [358,359,360,361], and these results possibly support the Ω c (3050) and Ω c (3119) as exotic heavy pentaquark baryons. See Refs.…”
Section: 23mentioning
confidence: 63%